134 Staying ahead of the curve – lessons in Covid-19 pandemic preparedness from Gibraltar. (16th November 2020) - Kumar, Arvind; Burke, Derek
Abstract : Gibraltar is a British Overseas Territory and has had a formal association with Great Britain since the Treaty of Utrecht in 1713. It has a population of around thirty-three thousand and shares a land border with Spain. The first reported case of Covid-19 in Gibraltar was reported on the 4th March 2020 from a Gibraltarian returning from Northern Italy. Early modelling completed by the Department of Public Health in March 2020 estimated the potential for five hundred Covid-19 related hospital admissions. St. Bernard's Hospital is the only hospital in Gibraltar and has a capacity of around one hundred and fifty beds. The key issues identified early on were identifying a venue of sufficient capacity to create a Covid-19 field hospital, oxygen requirements and the actual building of the facility. A recently completed sports facility was identified as being available which had sufficient capacity to provide spaces for three hundred beds. The major challenge was ensuring adequate oxygen delivery to the field hospital. As it was in a remote location, oxygen had to be sourced independently of the main hospital. An operational decision was made to only admit patients who required 5L/min oxygen or less. A contingency plan was made to ensure oxygen cylinders could be charged within Gibraltar at two units: a newly commissioned oxygen plant and the local hyperbaric unit. The field hospital was operational by the time of the expected surge in Covid-19 cases. An important lesson is that each field hospital will have differing specialist needs but have a backbone of common requirements. New hospitals will need staff, equipment and a physical space. However, during the Covid-19 pandemic an important issue that was flagged up early was the requirement for substantial amounts of oxygen. This helped to guide our team to build a specific hospital for a specific situation.